Analisa Perbandingan Penggunaan Metodologi Pengembangan Perangkat Lunak (Waterfall, Prototype, Iterative, Spiral, Rapid Application Development (RAD)) - Nur Adiya, Az Zahra Dwi; Anggraeni, Dea Lili; Ilham Albana (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
Methodology is a very important basic framework in the design and development of professional software, aimed at creating an information system that meets the business needs of an organization. Success in software development relies heavily on managing the software project as a whole. Establishing a methodology includes high dynamics in the design stages of a model that describes the activities and life cycle of a system. SDLC (Systems Development Life Cycle) or Systems Development Life Cycle, in the context of systems and software engineering, is a process that includes the creation and modification of systems, as well as the models and methodologies used to develop them. This discussion will explain the analysis of selecting software development methodologies, including waterfall, prototype, iterative, spiral, and rapid application development (RAD). It is hoped that the results of this discussion can provide considerations in choosing and using the right methodology based on each individual's needs, strengths and weaknesses, as well as other factors such as familiarity with technology, system complexity, system reliability, and short and precise time requirements, as well as referencing several scientific journals.